2019
DOI: 10.32598/rmm.7.2.51
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Non-Structural Gene of Influenza A Virus H1N1 in Iran

Abstract: Background: The Non-Structural (NS) genomic segment of influenza A virus expresses two proteins (NS1 and NS2) responsible for virulence and pathogenicity. Here, we characterize the NS gene of H1N1 influenza viruses isolated from Iranian patients during the 2015 and 2017 outbreaks. Materials and Methods: Influenza A positive specimens with high viral load were selected for virus amplification on MDCK (Madin-Darby Canine Kidney) cells to obtain sufficient viral RNA for RT-PCR. The NS segments were amplified and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…In some other studies bioinformatics methods were used to define the prevalence library and to study the trend of changes in HA and NA sequences of type A H1N1 influenza viruses from 2006 to 2013 10,11 . Further phylogenetic analysis on the NS gene of A/H1N1 isolates revealed that all Iranian isolates, except the A/Tehran/SMO08/2015, were close to strains from continental countries of Asia and North America, with 99% identity 12 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some other studies bioinformatics methods were used to define the prevalence library and to study the trend of changes in HA and NA sequences of type A H1N1 influenza viruses from 2006 to 2013 10,11 . Further phylogenetic analysis on the NS gene of A/H1N1 isolates revealed that all Iranian isolates, except the A/Tehran/SMO08/2015, were close to strains from continental countries of Asia and North America, with 99% identity 12 …”
Section: Introductionmentioning
confidence: 99%
“…10,11 Further phylogenetic analysis on the NS gene of A/H1N1 isolates revealed that all Iranian isolates, except the A/Tehran/SMO08/2015, were close to strains from continental countries of Asia and North America, with 99% identity. 12 Phylogeography is the study of historical processes that may have shaped the current geographical distribution of living species, such as viruses. Nowadays, these studies are performed according to the information obtained from the genealogy.…”
mentioning
confidence: 99%